Research and Development for Increasing the Capacity of the Cassava Tubers Cutting Machine - Suvanapa, Kiatsuda; Wongpichet, Seree (Journal of Applied Research on Science and Technology (JARST), 2019)
In chopping the rhizome of cassava to separate the tubers from the stems is one step that important for cassava harvesting. Currently, it still requires human labor. Therefore, research and development of the cassava tubers cutting machine to replace human labor still has a low working rate when compared to human labor. Therefore, this study has conducted research and development to increase the rate of working of cassava rhizome. By Kiatsuda Suvanapa and Seree Wongpichet, (2015) developed to have 2 feed boxes (2 feeders) and analyze with the flow chart of the various activities in the operation of the machine, it was found that the average operating rate is 68 trees/hour/person (147 kg/hr/person). After that, the above results can be used to design and build a new machine with 6 feeders (used by 2 people) and from the testing of the machine with cassava Kasetsart 50 varieties to compare with human labor. Found that the developed machine has an average operating rate of 353 plants/hour/person (1,124 kg/hr/person), which is 3 times faster than human labor and has lost cassava meat due to not all chopping average 0.78 %.